Pengaruh Efikasi Diri, Keaktifan Berorganisasi, Lingkungan Keluarga dan Locus of Control terhadap Kesiapan Kerja Mahasiswa Universitas Negeri Padang di masa Pandemi Covid-19 - Riska Adilah Nasution; Rita Syofyan; Jean Elikal Marna (Jurnal Ecogen, 2022)
The purpose of this study was to determine the effect of self-efficacy, organizational activity, family environment and locus of control on the work readiness of Padang State University students during the Covid-19 pandemic. This type of research was an associative descriptive study with a population of 100 Padang State University students. The sampling technique is proportional random sampling with a sample of 100 students. Data collection techniques are carried out by distributing questionnaires. To ensure the questionnaire used in this study, validity and reliability tests were used. The data analysis technique used is path analysis with the help of SPSS 24. Before performing the data analysis technique, the classical assumption test is carried out using the normality test and homogeneity test. The results of the research on sub structure 1 show that the variables of self-efficacy, organizational activity and family environment have a positive and significant effect on the locus of control of Padang State University students. And the results of research in sub structure 2 show that the variables of self-efficacy and locus of control have a positive and significant effect on work readiness of Padang State University students while the variables of organizational activity and family environment are not proven to have a significant effect on work readiness of Padang State University students. Keywords: self-efficacy, organizational activity, family environment, locus of control, job readiness